The affective post-prison - Johns, Diana (Criminological encounters, 2023)
In this piece I explore spaces and practices of carcerality in and through which prisoner identities are carried, reproduced and reconstituted beyond the prison. I show how prison leaks into the community by clinging to bodies, habits and identities, and how prisoner ways of being are carried physically, socially and symbolically. I show, too, how these ‘post-prison’ forms gather and manifest in places and spaces of exclusion, repetition and performance. I explore how those spaces are inhabited as an ongoingly interstitial form of carcerality - a liminal state of inbetweenness - that keeps people imprisoned even after they have been physically released; people can be no-longer-imprisoned, yet not quite free. From this perspective, the post-prison can be imagined as the affective shadow of the prison. I use the concept of assemblage to trace the material and semiotic lines that flow from the prison into these spaces - the in-between places - to show how the prison shadows people’s lives, how prison shadows linger, and how these lingering shadows constitute the affective post-prison. To convey the sense of being caught or suspended in this shadow place of carceral liminality, I draw on interviews with formerly imprisoned men and post-release support workers in Australia.